PS 06-15 HEMOGLOBIN CONCENTRATIONS AND HYPERTENSION INCIDENCE: A POPULATION-BASED COHORT STUDY. (September 2016) - Kim, Na Hyun; Lee, Ju-Mi; Kim, Hyeon Chang; Lee, Joo-Young; Yeom, Hyeung Seon; Lee, Jung Hyun; Suh, Il
Abstract : Objective: To investigate cross-sectional and longitudinal associations between serum hemoglobin concentration and hypertension in a Korea population. Design and Method: Between 2006 and 2013, we examined 4899 participants with mean age 56.6 (27–88 years) from a rural community. We excluded 298 participants with a history of myocardial infarction or stroke and 390 participants with very low hemoglobin levels (men <13.3 g/dl and women <11.6 g/dl). Finally, we performed a cross-sectional analysis on 1629 men and 2708 women. Longitudinal associations were evaluated in 654 men and 1099 women, after excluding 2584 people with hypertension at baseline and/or those who did not participate in follow-up examinations. Hypertension was defined as systolic blood pressure ≥ 140 mmHg, diastolic blood pressure ≥ 90 mmHg, or use of antihypertensive treatment. Results: Mean hemoglobin level was significantly higher in people with hypertension than in those without hypertension (p = 0.002 for men, p = 0.006 for women). In cross-sectional analysis, the odds ratio (95% CI) for hypertension per one standard deviation (SD) increase in hemoglobin concentration (1.2 g/dl) was 1.11 (1.05–1.18) before adjustment and 1.22 (1.11–1.34) after adjusting for age, sex, body mass index, lifestyle factors, and comorbidities. In longitudinal analysis, the relative risk (95% CI) for incident hypertension per one SD increase in hemoglobin concentration was 1.09 (0.96–1.23) before adjustment and 0.92 (0.79–1.09) after adjusting for age, sex, body mass index, lifestyle factors, baseline blood pressure, and baseline comorbidities. Conclusions: This study suggests that hemoglobin level is positively associated with high blood pressure, but not with incident hypertension Figure. No caption available.